Improving Student’s Speaking Skill Using Role Play Method at SMA Negeri 3 Malang - SYAIFURRAHMAN SYAIFURRAHMAN; Nissa Mawarda Rokhman (EDUCAFL : Journal of Education of English as Foreign Language, 2020)
Students need to master the speaking skill because it is one of the four language skills. There are so many factors influence the speaking skill of the students. Some factors come from the teacher and some others come from the student itself. Many teachers find the difficulties how to attract student speak English naturally. Besides, almost of students in Senior High School are shy and afraid to speak. We try to offer the role play technique in teaching speaking. By using role play technique, we hope students can join the activity learning well. Role play can result in repetition of speaking activity by providing a change. In short, role play covers a wide range of possibilities because in this technique students have to enter into many different situations. Moreover, it can help students to achieve maximum communication.